Бабенко В. О. та дослідження археологічного комплексу в с. Верхній Салтів - Чернігова, Н.В. (Археологія, 2000)
У статті розглядаються праці В. О. Бабенка, присвячені дослідженню Верхньосалтівського археологічного комплексу. Автор робить спробу висвітлити внесок ученого у вивчення епонімної пам'ятки салтівської культури та у середньовічну археологію взагалі. В 1900 г. учителем Василием Алексеевичем Бабенко и крестьянином Василием Капиносом был открыт знаменитый катакомбный могильник в с. Верхний Салтов бывшего Волчанского уезда Харьковской губернии. Его материалы были вовлечены в решение обширного круга актуальных вопросов, связанных с историей и археологией Хазарского каганата. В дальнейшем исследователь увязал катакомбный могильник с близлежащим городищем и провел изучение последнего. Он пришел к выводу о том, что памятник принадлежит хазарам и что городище было построено греческими мастерами по приглашению правителей Хазарского каганата. В. А. Бабенко попытался дать анализ материальной культуры каганата. В итоге он сделал несколько открытий, важных для развития хазароведения, и выдвинул ряд гипотез, актуальных и в настоящее время. In 1900, the teacher Vasyl Oleksi’ovych Babenko and a peasant Vasyl Kapinos discovered the famous catacomb burial ground at the village of Verkhnii Saltiv of the former Volchansk district, the Kharkiv province. Its materials were involved in the solution of a wide circle of topical problems related to the history and archaeology of the Khazar Khaganate. Then the researcher assumed the relation of the catacomb burial ground with the nearest settlement and studied the last. He concluded that the monument belonged to the Khazars and the settlement was constructed by Greek masters by invitation of the rulers of the Khazar Khaganate. Babenko tried to analyze the material culture of the Khazar Khaganate. As a result, he made a number of discoveries important for the development of the study of the Khazars and advanced several hypotheses topical up to now.